Central Eurasia : prize or quicksand? : contending views of instability in Karabakh, Ferghana and Afghanistan - Weisbrode, Kenneth; International Institute for Strategic Studies (Oxford ; New York : Oxford University Press for the International Institute for Strategic Studies, 2001)
"A decade after the demise of the Soviet Union, the newly independent states to Russia's south remain poor and remote from the developed world. Living standards have fallen throughout the region, while the energy wealth envisioned in the mid-1990s never materialised. Most governments have grown more corrupt and less stable. Responsibility for this state of affairs rests partly on an exaggerated and misplaced view, particularly popular among influential Western analysts, that the region is a natural, or even desirable, setting for imperial conflict. This view has skewed the policies of local actors away from much needed cooperation with one another and with more powerful neighbours. The major powers with interests in Central Eurasia - particularly the US - need to re-examine their fundamental assumptions about the region and what they want from it. Until they do, neither peace nor development will be possible and conditions will only deteriorate."--Jacket.
New area on the map -- Karabakh and the South caucasus -- Ferghana and Central Asia -- Afghanistan.
Includes bibliographical references (pages 87-96).
Keywords: Since 1900; Nagorno-Karabakh Conflict, 1988-1994.; Ethnic conflict -- Fergana Valley; Political stability -- Asia, Central; Social conflict -- Asia, Central; Social conflict -- Caucasus; Political stability -- Caucasus; Civil war -- Afghanistan; Geopolitics -- Caucasus; Geopolitics -- Asia, Central; Conflict management -- Asia, Central; Conflict management -- Caucasus; Intervention (International law); Petroleum industry and trade -- Asia, Central; Petroleum industry and trade -- Caucasus; Conflit du Nagorno-Karabakh, 1988-1994.; Petroleum industry and trade; Intervention (International law); Geopolitics; Conflict management; Civil war; Ethnic conflict; Politics and government; Political stability; Social conflict; Fergana Valley -- Politics and government -- 20th century; Afghanistan -- Politics and government -- 1973-; Afghanistan -- Politics and government -- 1989-2001.; Asia, Central -- Strategic aspects; Caucasus -- Strategic aspects; Asia, Central -- History -- 1991-; Asia, Central -- History -- 1991-; Asia, Central -- Strategic aspects; Asia -- Fergana Valley; Caucasus; Asia, Central -- Politics and government -- 1991-; Caucasus -- Politics and government; Nagorno-Karabakh (Azerbaijan) -- Politics and government; Caucasus -- Foreign relations; Nagorno-Karabakh (Azerbaijan) -- Foreign relations; Farghona (Uzbekistan) -- Foreign relations; Afghanistan -- Foreign relations; Book; History